Mental Workload Assessment: The Relationship Between Physiological Heart Rate Variability and Subjective NASA-TLX Measures - Sutarto, Auditya Purwandini; Izzah, Nailul; Kusumawardani, Rahma Indah (Journal of Health Sciences and Medical Development, 2024)
The rapid advancement of technology has shifted many jobs to be dominated by mental or cognitive activities. Consequently, it is essential to measure mental workload (MWL) to ensure it does not exceed workers' capacity, which could increase error rates, pose safety risks, reduce productivity, and worsen well-being. This study aims to investigate the relationship between objective and subjective measures of mental workload. Using an experimental approach, HRV physiological signals were recorded from 30 subjects under four different conditions: baseline, MWL test 1 ("d2 attention" test), MWL test 2 ("switcher featuring" test), and recovery. Subjects were also asked to complete the NASA-TLX questionnaire to assess their perceived mental workload levels during the "d2 attention" and "switcher featuring" tests. The results of the repeated measures ANOVA showed significant differences in six HRV parameters across the four conditions. However, post-hoc tests revealed that only heart rate was able to distinguish between the two MWL tests. While NASA-TLX was sensitive enough to differentiate mental workload levels between the two types of tests, no significant correlations were found between each HRV index and NASA-TLX. This suggests a discrepancy between the two types of measures. Further studies are needed to employ different types of tests as well as other physiological measures.